Ecological Diversity and Contribution of Edible Insects to Household Food Security: Insects for Food and Feed - Ojala, Martin; Magwanga, Richard; Okuto, Erick; Muok, Benard; Kipyegon, John (International Journal For Research In Agricultural And Food Science, 2022)
Food insecurity is compounded by the impact of climate change as well as increased human population. Even though, several African countries have put tremendous efforts in improving food security but the output is still limited. Diversification could be the key to unravel the problem of food insecurity; moreover, the use of insects for food has a long history. Insects are rich source of protein and at the same time provide essential nutrients With Greater contribution in reducing the complications of malnutrition. In this study, the researchers sought to investigate the contribution and ecological diversity of edible insects by mapping their ecological niches within and around Kakamega tropical Rainforest. The communities around the rainforest have a long tradition of using various insects as food. The study adopted a structured questionnaire which was administered to 209 households in the months of April and September, during the long and short rainy seasons, respectively. The forest ecosystem was stratified into five zones, namely dense forest, riverine, forest edge, open grassland and hills. Plant sampling was done within the forest strata using transect for species identification. Plants where insects were spotted were counted and recorded. A total of 88 insect species from 30 families and 13 orders were obtained whereas 97 food plants from 42 families were also observed. The families Nymphalidae were the most abundant which was closely followed by the Apidae family. The study showed that there was high species diversity of both insects and plants within the dense forest than the rest of study sites. This is attributed undisturbed nature of the habitat.